SPATIAL CHARACTERIZATION OF TELECOMMUNICATION SATELLITES VISIBLE ABOVE THE REPUBLIC OF SERBIA - Đukanović, Slaviša; Mladenović, Vladimir; Gligorijević, Milan; Milošević, Danijela; Radojević Aleksić, Ivona (Bulletin of Natural Sciences Research, 2020)
This paper deals with the general technical, spatial, and temporal characteristics of satellite telecommunications systems. Particular attention was paid to the peculiarities of the territory of the Republic of Serbia in terms of implementation and use of modern satellite telecommunication infrastructure. The overview shows how and on which way to use various satellite telecommunication systems to configure and exploit next-generation networks, especially modern communications such as 5G technology and IoT. Their work cannot be imagined without the high speeds and high frequencies that allow us to transmit a wealth of information - from short messages/news to HD video on a mobile phone. We need either a base station network or in the case of the high seas or areas where the base station system is difficult to imagine, we need satellite communication. The paper presents data that give a numerical and graphical overview of geostationary satellites visible from the territory of the city of Belgrade, depending on the orbital position and the associated angle of azimuth and elevation, which would also be valid for the leading territory of Serbia.
Keywords: Satellite’s orbites; 5G technologies; IoT; Azimuth; Elevation